Polariton-drag enabled quantum geometric photocurrents in high symmetry materials - Xiong, Ying (2023)
Lowered symmetry enables access to a wide set of responses not typically accessible in high symmetry materials. Prime examples are time-reversal forbidden quantum geometric photocurrent responses (e.g., linear injection and circular shift photocurrents) that are thought to vanish in non-magnetic materials. Here we argue that polariton-drag processes enable to unblock such quantum geometric photocurrents even in non-magnetic and centrosymmetric materials. Strikingly, we uncover how a cooperative effect between finite q irradiation and the Fermi surface position leads to a polariton selective photoexcitation (PSP). PSP enables to directly address carriers within tight momentum resolved windows of the Fermi surface to yield giant enhancements of quantum geometric photocurrents. This selectivity enables to directly track momentum resolved quantum geometric quantities along the Fermi surface providing a new tool to interrogate the quantum geometry of high symmetry materials.